Consciousness towards Socio-Economic Impact Propensity: The Langkawi Island - A. Khadar, Nur Zafirah; Jaafar, Mastura; Mohamad, Diana (EDP Sciences, 2014)
This study evaluates the socio-economic impact of tourism development on the tourist perceptions in Oriental Village, Langkawi Island. Socio-economic impacts are the consequences of either the tourism industry development or the presence of tourists in a particular destination, which resulted from the host-tourist relationship. Data for this research was generated using quantitative techniques and divided into 3 parts of instruments. Part A includes the demographic profile of respondents, Part B contains perceptions and opinions in economic and social impatcs and the last part was Part C where consists tourism utility assessment in social, economy and transportation. Simple frequency of mean and paired sample -test analysis were used to analyse the data generated for the study. The findings of the analysis proved that tourism development had a significant effect on the socio-economic impact and on the tourists’ perceptions in Oriental Village, Langkawi Island. In addition, it is viewed that public participation must be encouraged by tourism developers and planners to ensure the sustainability of tourism development in the community. Thus, this paper aims to give emphasis on the establishment of standard social guidelines within the tourism development framework for the purpose of preserving and protecting the social and economic values.